مملكة موريطانيا خلال حكم الملكين يوبا الثاني وبطليموس - عقاب, ابتسام; حتيري, حنان (جامعة الوادي - University of Eloued, 2023)
تعد مملكة نوميديا من اهم الممالك الحضارية في بلاد المغرب القديم, وذلك لموقعها الاستراتيجي المميز, إلى جانب التركيبة السكانية التي شكلت محورًا هامًا في حضارة نوميديا, وهذا ما جعل لها عدة تسميات مختلفة من طرف المؤرخين والتي من أشهرها نومادوس, أما الحياة السياسية في نوميديا قبل حكم يوبا الثاني, فقد كان الحكم فيها متسلسل من طرف الحكام الذين سبقوه, كما كانت لهم انجازات مختلفة سواء كانت في الجاني السياسي أو غيره, إلا أننا لا ننسى كلما يحكم ملك يتبع سياسة أبيه إلى وفاته, وبعده يحكم ابنه, ومن بين انجازات الحكام قبل يوبا الثاني : توحيد نوميديا وضمان استقلاليتها, إلى جانب النمو الحضاري في عهده, أما يوبا الثاني الذي كان من أهم الشخصيات في نوميدياوموريطانيا وذلك من خلال عصره الذهبي المتميز بالعديد من الانجازات والاهتمامات في الجوانب المختلفة, وخاصة في الجانب الثقافي برز كعالمًا أكثر من ملكًا, وعند وفاته سنة 23م, خلفه ابنه بطليموس الحكم وهو آخر ملوك موريطانيا, تميز عصره في بعض الاهتمات في الجانب الاقتصادي خاصة في الصيد البحري, والمصانع الارجوانية. The Kingdom of Numidia is considered one of the most important civilized kingdoms in the ancient Maghreb, due to its distinguished strategic location, in addition to the population composition that formed an important axis in the Numidia civilization, and this is what made it several different names by historians, the most famous of which is Nomadus. As for the political life in Numidia before The rule of Yuba II, the ruling was sequential by the rulers who preceded him, as they had different achievements, whether in the political offender or otherwise, except that we do not forget whenever a king rules, follows the policy of his father until his death, and after him rulesHis son, and among the achievements of the rulers before Yuba II: the unification of Numidia and the guarantee of its independence, along with the civilizational growth during his reign. As for Yuba II, who was one of the most important personalities in Numidia and Mauritania, and that was during his golden age distinguished by many achievements and interests in various aspects, especially in the aspect Al-Thaqafi emerged as a scholar more than a king, and upon his death in the year 23 AD, his son Ptolemy al-Hakam, the last king of Mauritania, against the dollar by one unit, the lower the trade balance b (0.022), during the study period.
مذكرة ماستر تاريخ تخصص حضارات قديمة
Keywords: نوميديا- موريطانيا- يوبا الثاني- بطليموس; Numidia - Mauritania - Juba II - Ptolemy